(3TQM CfhGQ GdSQGFO hSQGFO GdCfhGQs - (3CMeO Hf jhSa Hf eMeO Hf jhSa GdaGSis; (3JGL GdOjf CHh GdYHGS CMeO Hf eMeO GdHcjQ GdTQjTjs ((3eOjfI aGS s)
(3ChdgG (B:s
,(3HYO adeG cGfJ GdbUjOI GdeSeGI HCfhGQ GdSQGFQ hSQGFQ GdCfhGQ s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hGNjQkG hGdUdGI hGdSdGe Ydi SjOfG hfHjfG hehdGfG eMeO NGJe GdfHjjf (B,(3GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3CfhGQ GdSQGFQ hSQGFQ GdCfhGQ ddTQHTi GfXQ EjVGM Gdecfhf L(B1 (3U` (B144s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs